Quantitative Investigations of Polygonal Patterned Ground in Continental Antarctica: A Mars analogue - Sassenroth, C.; Hauber, Ernst; de Vera, Jean Pierre Paul; Schmitz, Nicole (2017)
Polygonal fractured ground is widespread at middle and high latitudes on Mars. The latitude-dependence and the morphologic similarity to terrestrial patterned ground in permafrost regions may indicate a formation as thermal contraction cracks, but the exact formation mechanisms are still unclear. This study quantitatively investigates polygonal networks in icefree parts of continental Antarctica to help distinguishing between different hypotheses of their origin on Mars.